Comparative Evaluation of Using Intranasal Desmopressin, Parenteral Diclofenac or their Combination in the Management of Acute Renal Colic Pain in Iraqi Patients - A. Majeed, Ibrahim (Iraqi Journal of Pharmaceutical Sciences, 2017)
There is a suggestion that an antidiuretic hormone-induced decrease in diuresis might contribute to the rapid relief of the acute pain in renal colic. This study was designed to evaluate the efficacy of desmopressin nasal spray compared with diclofenac given intramuscularly in patients with acute renal colic. The study included 75 patients randomized into three different groups; group A received desmopressin (40 Î¼g, nasal spray), group B diclofenac (75 mg) intramuscularly and group C, both desmopressin and diclofenac. Pain was assessed using a visual analogue scale (a 10-cm horizontal scale ranging from `no pain' to `unbearable pain') at baseline, 10, 20 and 30 min after administering the treatments. On admission, the pain level was the same in all three groups. At 10 min the pain decreased in all groups to a level that was not significantly different. At 20 min groups B and C had similar mean pain levels (5.8), whereas in group A it was 5.7. At 30 min, groups B and C scored 3.0 and 2.5 respectively, and group A 6.1. All three treatments were equally effective at 10 and 20 min but at 30 min there was a stabilization/slight increase in pain level in group A. In conclusion, these results indicate that desmopressin may be used to treat renal colic either alone or combined, increasing the analgesic effect of other drugs like diclofenacKey words: renal colic, intranasal desmopressin, diclofenac